"At the extremities of life" – Service user experiences of helpful help in mental health crises. Issue 2 (3rd April 2017) - Klevan, Trude; Karlsson, Bengt; Ruud, Torleif
ABSTRACT: Mental health services have recently undergone a transition from institution- to community-based care, and crisis resolution teams (CRTs) represent a community-based service that targets users experiencing an acute mental health crisis. The current study was undertaken to explore the service user experiences of helpful help provided by CRTs in a mental health crisis context. Semistructured in-depth interviews were conducted with 14 service users to elucidate how mental health crises are experienced as devastating and multilayered events. Suicidal thoughts and/or intentions were commonly reported, seemingly regardless of whether the crisis was related to a serious mental illness. The important issues relating to help that were emphasized by the participants in this study were practical support and help with daily structure, establishing a foundation of safety, and strengthening the sense of self. The authors elaborate in the discussion on how these different issues of help are connected, showing that practical help plays an important role in supporting self-worth and the sense of safety, but that practical and structural issues have been rarely addressed by CRTs, at least in the context of this study. Thus, a broadened and social contextual-oriented perspective on mental health crises is important in developing helping practices that are perceived as more recovery oriented and helpful.